Analysis Final Semester Exam Questions For Physical Education, Sports, And Health Learning Junior High School Level In South Bengkulu Regency - Muhammad Aufa Rafiqi; Candra Kurniawan; Riyan Jaya Sumantri; Surisman (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
This research evaluates the quality of Physical Education, Sports, and Health (PJOK) final examination items across junior high schools in South Bengkulu Regency. Utilizing a quantitative descriptive approach, the study assessed five key psychometric properties: validity, reliability, difficulty index, discriminating power, and distractor efficiency. Data were gathered from 128 students across five schools through documentation, interviews, and observations. Findings indicate that a significant portion of the test items failed to meet standard quality benchmarks, characterized by low validity, disproportionate difficulty levels, and weak discriminating power. The study concludes that the PJOK assessment instruments in this region necessitate a comprehensive overhaul to align with professional testing principles.